(untitled) (Eurasian Journal of Philology Science and Education, 2018)
In the article language units and figurative words of the Turkic/Slavic languages containing the seme ‘dog’ from the point of ethnolinguistics are considered. The informative value of cynomorphisms in the Turkic/Slavic languages will be disclosed on the basis of lexicographic sources. They are the cultural-national phrases describing national feature. As the figurative perception received in the result of influence of daily living and subjects and phenomena on each other which surround us is related to formation of proverbs. These language units were saved only in the material and spiritual culture transferred from generation to generation. In many cases in empirical perception of animals the image of dog becomes difficult to be defined from the mythological point. It expands semantic potential and enriches a cultural connotation of the main word.